Comparative study of community medicine practice in MBBS curriculum of health institutions of Nepal - Marahatta, SB; Sinha, NP; Dixit, H; Shrestha, IB; Pokharel, PK (Kathmandu University Medical Journal, 2010)
Background: A revolution in health care is occurring as a result of changes in the practice of medicine and in society. Medical education, if it is to keep up with the times, needs to adapt to society's changing attitudes. Presently medical education has been criticised for its orientation and insensitivity to people's need. The MBBS curriculum of medical institutions of Nepal has been focusing on community-based approaches and is still guided by the same notion. The question put forward is whether it has been appropriate to nurture the present health needs and aspiration of people. Objective: The objective of the present study is to review the existing community based medical education in health institutions of Nepal to strengthen the components of community care. Materials and methods: Qualitative study was done by reviewing the curricula and existing community medicine courses/activities in MBBS curriculum of Institute of Medicine (IoM)/Tribhuvan University, BP Koirala Institute of Health Sciences (BPKHIS) and Kathmandu University School of Medical Sciences (KUSMS). Findings and Discussion: The curriculum of all the health institutions have addressed significantly on community medicine practice. As per Institute of Medicine, the community medicine practice is achieved through community based learning experiences like community diagnosis, concurrent field with families of sick members and district health system management practice. In BP Koirala Institute of Health Sciences, community medicine practice is undertaken through exposure to community diagnosis program, health care delivery system, family health exercise, applied epidemiology and educational research methodology, management skills for health services and Community Oriented Compulsory Residential Rotatory Internship Program (COCRRIP). In KUSMS, community medicine module is carried out as- community diagnosis program, community health intervention project, school health project, occupational health project, health delivery system functioning, family health care activities and Compulsory Residential Rotatory Internship Program in outreach clinics. In the practice the practical aspects are largely unstructured that waste too much time in non-educational activities and rely on learning and doing. Meanwhile, expectation of the community is increasing and the challenge of nurturing their demands has come in forefront. Community has perceived that the medical schools are concentrating on fulfilling the demand of their curriculum rather directing on their health care need. Conclusion: Health institutions need to be accountable to take the responsibility of strengthening the health status of the community of their catchments areas. The practice of community medicine need to be done in an innovative way and these schools should execute continual intervention activities and complement other institutions working in their areas. Key words: Community medicine; curriculum; field practice DOI: 10.3126/kumj.v7i4.2775 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 461-469